Sa‐Lrp from Sulfolobus acidocaldarius is a versatile, glutamine‐responsive, and architectural transcriptional regulator. Issue 1 (16th December 2012) - Vassart, Amelia; Van, Marleen; Orell, Alvaro; Hong, Ye; Peeters, Eveline; Albers, Sonja‐Verena; Charlier, Daniel
Abstract Sa‐Lrp is a member of the leucine‐responsive regulatory protein (Lrp)‐like family of transcriptional regulators in Sulfolobus acidocaldarius. Previously, we demonstrated the binding of Sa‐Lrp to the control region of its own gene in vitro. However, the function and cofactor of Sa‐Lrp remained an enigma. In this work, we demonstrate that glutamine is the cofactor of Sa‐Lrp by inducing the formation of octamers and increasing the DNA‐binding affinity and sequence specificity. In vitro protein‐DNA interaction assays indicate that Sa‐Lrp binds to promoter regions of genes with a variety of functions including ammonia assimilation, transcriptional control, and UV‐induced pili synthesis. DNA binding occurs with a specific affinity for AT‐rich binding sites, and the protein induces DNA bending and wrapping upon binding, indicating an architectural role of the regulator. Furthermore, by analyzing an Sa‐lrp deletion mutant, we demonstrate that the protein affects transcription of some of the genes of which the promoter region is targeted and that it is an important determinant of the cellular aggregation phenotype. Taking all these results into account, we conclude that Sa‐Lrp is a glutamine‐responsive global transcriptional regulator with an additional architectural role.